How Are Temporary Absences and Work Releases Being Used With Canadian Federal Offenders?. Issue 1 (1st January 2019) - Ternes, Marguerite; Helmus, L. Maaike; Forrester, Trina
ABSTRACT: Temporary absences (TAs) and work releases (WRs) allow inmates to leave the institution for short periods of time and are generally a first step in the process of gradual community reintegration. To better understand how TAs and WRs are being used with Canadian federal inmates, this study examined patterns in type, length, success rates, frequency, and timing throughout the inmates' sentences. Using all 355, 223 absences granted between 2005 and 2013, study 1 examined common descriptive information for absences over time, including analyses by reasons, group absences, and failure rates. Study 2 used two data sets. The first consisted of 27, 098 inmates released between 2005 and 2011. The second included 7, 341 inmates who began their sentences between April 1, 2005, and March 31, 2013, and participated in a TA or WR. Of all TAs granted during the study period, more than 90% were escorted. Escorted absences tend to be granted earlier in an inmate's sentence than unescorted absences or WRs. Inmates participating in more than one absence type were likely to have more absences overall. Almost all inmates on absences returned to the institution without incident, indicating that they are safe initiatives for the community. Findings are compared to patterns of use from the 1990s and implications regarding granting decisions are discussed.